Characteristics of MRAS based induction motor sensorless vector control system taking into account iron loss - Tsuji, M.; Fujin Xu; Tsuruda, Y.; Hamasaki, S.-I.; Shuo Chen (2009 International Conference on Electrical Machines and Systems : 15-18 November 2009, 2009)
We have proposed a current observer-based speed sensorless vector control system taking into account both iron loss and stator resistance identification. The method is constructed in a synchronously rotating reference frame. The effectiveness of the proposed system has been investigated by digital simulation and experimentation. Furthermore important control parameters such as stator resistance, observer gain and filter of speed estimation are studied by comparing the computed result with experimental one.